2004
DOI: 10.1111/j.0013-9580.2004.54302.x
|View full text |Cite
|
Sign up to set email alerts
|

Correlation between 1H MRS and Memory before and after Surgery in Mesial Temporal Lobe Epilepsy with Hippocampal Sclerosis

Abstract: Summary:  Purpose: Proton magnetic resonance spectroscopy (1H MRS), which can demonstrate neuronal loss and gliosis, may be used as a sensitive tool for lateralization of temporal lobe epilepsy (TLE). Although the correlation between the memory functions and 1H MRS has been investigated, its predictive value after surgery has not been studied previously. This study evaluated memory and 1H MRS values of medically intractable patients with mesial TLE and hippocampal sclerosis (MTLE‐HS) before and after selective… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
16
0
1

Year Published

2004
2004
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(19 citation statements)
references
References 26 publications
2
16
0
1
Order By: Relevance
“…An event-related potential study showed the involvement of hippocampal formation and amygdala during verbal learning and memory, and amnesic patients with hippocampal lesion present greater impairment in declarative than in procedural memory [64,65]. In the literature, left HS was correlated with deficiency of verbal, right HS with impairment of visuo-spatial memory, and the severity of memory deficits was related to the degree of HS detected with MRI or 1 H MRS [41][42][43]. In addition, the degree of pyramidal cell loss in Ammon's horn and loss of hilar neurons and granule cells of the dentate gyrus correlated to memory impairments [44,45,[47][48][49].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…An event-related potential study showed the involvement of hippocampal formation and amygdala during verbal learning and memory, and amnesic patients with hippocampal lesion present greater impairment in declarative than in procedural memory [64,65]. In the literature, left HS was correlated with deficiency of verbal, right HS with impairment of visuo-spatial memory, and the severity of memory deficits was related to the degree of HS detected with MRI or 1 H MRS [41][42][43]. In addition, the degree of pyramidal cell loss in Ammon's horn and loss of hilar neurons and granule cells of the dentate gyrus correlated to memory impairments [44,45,[47][48][49].…”
Section: Discussionmentioning
confidence: 99%
“…In addition, deficiency of verbal memory in left HS and deficiency of visual memory in right HS were observed in patients with early-onset, long-term duration and highfrequency of seizures [42]. Proton magnetic resonance spectroscopy ( 1 H MRS), which is assumed to be suitable for providing information about neuronal loss and gliosis, revealed correlation between 1 H MRS values and verbal memory scores [43]. Postoperative histological studies showed that pyramidal cell loss in the removed hippocampal formation significantly correlated with preoperatively detected memory impairments of patients [44][45][46][47][48][49].…”
Section: Introductionmentioning
confidence: 99%
“…Data from baseline neuropsychological tests (Chelune et al, 1991; Davies et al, 1998; Jokeit et al, 1997) and the intracarotid amobarbital procedure (IAP) (Bell et al, 2000; Chiaravalloti and Glosser, 2001; Kneebone et al, 1995; Loring et al, 1990) have been found to predict some of the variance in postoperative memory function. Similarly, preoperative measures of hippocampal integrity including direct recordings from hippocampal neurons (Cameron et al, 2001), 1H MRS (Hanoglu et al, 2004) and hippocampal volumes and T2 relaxation times derived from preoperative MRI studies have been shown to predict some aspects of postoperative memory function (Baxendale et al, 1998; Wendel et al, 2001). More recently, a number of functional imaging paradigms have shown some promise in the prediction of both postoperative decline in both visual (Janszky et al, 2005) and verbal (Richardson et al, 2004) memory skills.…”
mentioning
confidence: 99%
“…There are progressive behavioral changes including increasing memory deficit. Progressive memory impairment was notable in patients whose seizures were intractable, which suggested frequent seizures contributed this memory loss 15. Contralateral spikes on interictal EEG can appear along with the duration of epilepsy.…”
Section: Mtle With Hsmentioning
confidence: 99%